Rejuvenation of Pesticide Polluted Soil from the Isolated Microbial Flora of Agricultural Field - Sivakumar, J. (Asian Journal of Science and Applied Technology, 2023)
The widespread use of pesticides leads to imbalances in the qualities of soil, water, and air environments. Pesticides can only be broken down more quickly by combining microbial consortia of native and naturally occurring bacteria isolated from certain polluted environments. To rejuvenate the pesticide polluted soil, the samples was collected and microbial flora were isolated from the soil samples. These floras were introduced into the three pesticides like Carbaryl, Monocrotophos and Malathion (CMM) for the biodegradation activity. Standard microbiological protocols were followed to isolate the microbial flora from the collected soil samples. The isolated microbial strains were confirmed with the isolation of genomic DNA. The biodegradation of pesticides such as Carbaryl, Monocrotophos and Malathion (CMM) were performed with the isolated strains. The bacterial strains such as Pseudomonas sp, Bacillus sp and Micrococcus sp; actinomycetes – Azatobacter; fungal species such as Aspergillus fumigatus, Gliocladium sp and Humicola sp were isolated from the agricultural field. Among these Bacillus sp showed highest biodegradation activity against the three pesticides. These investigations screened the best microorganism for several pesticides, including carbaryl, Monocrotophos, and Malathion (CMM), the best degradation methods, and the best degradation environment, providing a more practical reference for subsequent study.